Diagnosis of viruses in potato plantations and their impact on the yield - Dunich, A.; Mishchenko, L.; Kyrychenko, S.; Bondus, R.; Kozub, N.; Mishchenko, I.; Pozhylov, I. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To diagnose potato virus Y (PVY) and potato leaf roll virus (PLRV) in potato plantations and determine the impact of the pathogens on plant yield. Methods. Visual diagnosis method, double sandwich enzyme-linked immunosorbent assay, reverse transcription-polymerase chain reaction, morphomentric and statistic methods were carried out in this study. Results. Among the varieties studied, the most common symptom was upward leaf rolling, with some varieties exhibiting mosaics with necrosis and leaf deformation when the others show leaf rolling with necrosis. Virus identification was carried out in different potato varieties. It was found that PVY was detected in 3 varieties, PLRV was revealed in 4 varieties, mixed infection of PVY + PLRV was confirmed in 2 potato varieties, the incidence was 27.3%, 36.4% and 18.2%, respectively.It was found that among all varieties of different maturity groups, the most pronounced harmful effect of viruses on yield was observed in early varieties. Moreover, exactly PLRV infection most significantly reduced such indicators as yield (g/bush), average weight of one tuber, and average weight of one marketable tuber or mixed infection PLRV + PVY (in the case of mid-early varieties) compared to PVY mono-infection (for early, medium- and late-maturing varieties). On the other hand, the presence of PVY in plants (in mono- or coinfection with PLRV) reduced the average number of tubers per bush more than PLRV for some varieties. Conclusions. Significant yield losses observed due to PVY, PLRV and PVY + PLRV coinfection indicate the need to use virus-free seed potatoes or varieties resistant to them.